Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(-2.\left(x+\frac{1}{3}\right)-5.\left(x+\frac{1}{3}\right)=\frac{1}{2}.x\) \(x\)
<=> \(\left(x+\frac{1}{3}\right).\left(-2-5\right)=\frac{1}{2}.x\)
<=> \(\left(x+\frac{1}{3}\right).\left(-7\right)=\frac{1}{2}.x\)
<=> \(-7x-\frac{7}{3}=\frac{1}{2}.x\)
<=> \(-7x-\frac{1}{2}.x=\frac{7}{3}\)
<=> \(\left(-7-\frac{1}{2}\right).x=\frac{7}{3}\)
<=> \(\frac{-15}{2}.x=\frac{7}{3}\)
<=> \(x=\frac{7}{3}:\frac{-15}{2}=\frac{-14}{45}\)
\(-7x-\frac{7}{3}=\frac{1}{2}.x\)
<=> \(-7x-\frac{1}{2}x=\frac{7}{3}\)
<=> \(\left(-7-\frac{1}{2}\right).x=\frac{7}{3}\)
<=> \(\frac{-15}{2}.x=\frac{7}{3}\)
<=> \(x=\frac{7}{3}:\frac{-15}{2}=\frac{-14}{45}\)
a, \(\dfrac{62}{7}.x=\dfrac{29}{90}.\dfrac{3}{56}\)
\(\dfrac{62}{7}.x=\dfrac{29}{1680}\)
\(x=\dfrac{29}{1680}:\dfrac{62}{7}\)
\(x=\dfrac{29}{14880}\)
b, \(\dfrac{1}{5}:x=\dfrac{1}{5}-\dfrac{1}{7}\)
\(\dfrac{1}{5}:x=\dfrac{2}{35}\)
\(x=\dfrac{1}{5}:\dfrac{2}{35}\)
\(x=\dfrac{7}{2}\)
c, \(\left(x+\dfrac{1}{4}-\dfrac{1}{3}\right):\left(2+\dfrac{1}{6}-\dfrac{1}{4}\right)=\dfrac{7}{46}\)
\(\left(x+\dfrac{1}{4}-\dfrac{1}{3}\right):\left(\dfrac{13}{6}-\dfrac{1}{4}\right)=\dfrac{7}{46}\)
\(\left(x+\dfrac{1}{4}-\dfrac{1}{3}\right):\dfrac{23}{12}=\dfrac{7}{46}\)
\(\left(x+\dfrac{-1}{12}\right):\dfrac{23}{12}=\dfrac{7}{46}\)
\(\left(x+\dfrac{-1}{12}\right)=\dfrac{7}{46}.\dfrac{23}{12}\)
\(x+\dfrac{-1}{12}=\dfrac{7}{24}\)
\(x=\dfrac{7}{24}-\dfrac{-1}{12}\)
\(x=\dfrac{3}{8}\)
1/5.2^x+1/3.2^x.2=1/5.2^7+1/3.2^7.2
2x(1/5+1/3.2)=2^7(1/5+1/3.2)
=>2^x=2^7
=> x=7
a; - \(\dfrac{1}{3}\).(15\(x-9\)) + \(\dfrac{2}{7}\).(- \(x-34\)) = 1 - \(\dfrac{3}{4}\).(-16\(x+4\))
- 5\(x\) + 3 - \(\dfrac{2}{7}\)\(x\) - \(\dfrac{68}{7}\) = 1 + 12\(x\) - 3
12\(x\) + 5\(x\) + \(\dfrac{2}{7}x\) = 3 - \(\dfrac{68}{7}\) - 1 + 3
17\(x\) + \(\dfrac{2}{7}x\) = (3 - 1 + 3) - \(\dfrac{68}{7}\)
\(\dfrac{121}{7}\)\(x\) = 5 - \(\dfrac{68}{7}\)
\(\dfrac{121}{7}\) \(x\) = - \(\dfrac{33}{7}\)
\(x\) = - \(\dfrac{33}{7}\): \(\dfrac{121}{7}\)
\(x\) = - \(\dfrac{3}{11}\)
Vậy \(x\) = - \(\dfrac{3}{11}\)